Estimation of water runoff and harvestability of the valley of Haliwat Basin, Western Desert using SCS-CN model - Gharbi , Moshtaq Ahmed; Salh , Abdulqader Mahdi; Khalaf , Mohmood Jameel (Brawijaya University, 2025)
The area under study is one of the dry climates, characterized by seasonal rainfall in the winter only. It also contains no stations for measuring the amount of rainwater that falls. Therefore, the study aimed to estimate the amount of rainwater falling using indirect mathematical methods to estimate the amount of water that can be stored behind the dams built in this valley, which will be reflected in the better management of this water and its sustainability for various uses. The final runoff values for the valley of Haliwat Basin were calculated based on the total annual rainfall and the maximum soil water retention potential (S) for 2023. The natural characteristics, including land uses, the degree of slope of the land surface, and the soil properties (HSG), were used to create a hydrograph curve to estimate the rainwater, from which the volume of water that can be stored in one season can be calculated. This depends on a set of main factors, namely the depth and volume of the water flow, the accumulation of water from the rain at the beginning of the rainfall, as well as what is lost from this rain due to evaporation and seepage into the ground, and what is absorbed by the plants. Through the measurements, the quantities of water flow varied between 50/m3 and 376/m3. The storage capacity of water in the areas of dams established within the valley basin was estimated at 14,363 m3/year.